Estudo das propriedades vibracionais e estruturais do cristal oxalato de l-histidina em função da pressão e da temperatura - PINHO, Ellen Karolyne da Silva (2018)
The complexation of amino acids and dicarboxylic acids has been the subject of research in recent years and the study of these materials subjected to extreme temperature and pressure demonstrates that these organic compounds have structural regeneration capacity. L-Histidine Oxalate (LHO) is a crystal formed from salts of L-histidine with oxalic acid that has not yet had its vibrational and structural properties investigated as a function of temperature and pressure. In this work, the LHO crystal was synthesized by the slow evaporation of the solvent in 1: 1 ratio of L-histidine and oxalic acid using deionized water as solvent, and recrystallizations were performed to improve the morphology and purity of the crystal. LHO crystal was investigated by X-ray diffraction (XRD) under conditions of temperature and ambient pressure, by Thermogravimetry/Thermogravimetry (TG/DTG), Differential Thermal Analysis (DTA), Differential Exploration Calorimetry (DSC) and Raman Spectroscopy as a function of Temperature and Pressure. XRD analysis and refinement by the Rietveld Method showed that the crystal crystallizes in the orthorhombic system, with spatial group P212121, with four molecules per unit cell (Z = 4). TG/DTG-DTA analyzes showed that the material undergoes a large loss of mass associated with fusion at 498 K and decomposes simultaneously into three stages. The vibrational and structural study by Raman Spectroscopy as a function of Temperature showed the stability of the material over a wide temperature range (8 to 483 K), without presenting significant structural changes. Raman Spectroscopy as a function of pressure (0.0 to 7.3 GPa) evidenced the occurrence of conformational changes in the range of 1.5 to 2.6 GPa, characterized by disappearance of two bands associated with lattice modes and little modifications linked to the internal modes. A second transition occurs around 5,1 GPa, characterized by strong changes related to both lattice and internal modes (particularly modes linked to the imidazole ring). In addition, the experiment indicated accommodation and definition of the new phase from the 6,9 GPa. Finally, the transitions undergone by the crystal were reversible.